Understanding the Perceptions of Secondary School Youth toward Agricultural Careers in Democratic Republic ofCongo, Kenya and Nigeria - Welissa Mawia Mulei; Bolanle Larinde; Adedayo Adefioye; Prince Bobo; Paul Lester Woomer (Journal of International Agricultural and Extension Education, 2020)
Youth are critical participants in the modernization of African agriculture but often their perception of farming is negative. A baseline survey of 1264 students from eight secondary schools in Democratic Republic(DR)ofCongo, Kenya and Nigeria was conducted to assess their attitudes toward career pathways to agriculture and agribusiness. KoboToolBox was used to collect data online before compilation and inspection for errors in Microsoft Excel and exportation into STATA for analysis. Findings were presented as summary statistics, frequencies and multiple linear regression. A large majority (86%) of the students attended agricultural courses and 54% identified agriculture as having a place in their future, but often not as their highest career ambition. Livestock, field cropping, small animal production, and horticulture were the most viable enterprises for the youngsters. Nearly half (46%) that were averse to agriculture as a career path based their decision upon excessive labor requirements (30%), difficulties in securing land (25%), and low returns to effort (20%). Disparities from a country, area and gender perspective were recorded. Perceptions and career plans among the sexes differed; with females having less experience with machinery, and were more drawn to horticulture and agro-processing. Despite unfavorable attitudes toward agriculture, the study established that youth from these countries recognize that opportunity exists from adopting modern farming methods and commercial agricultural enterprises. The results of this study suggest several avenues for future Start Them Early Program activities intended to strengthen career pathways toward agriculture in African secondary schools
Keywords: Africa; agricultural education; career pathways; Start The m Early Program; youth